Sentencing Transferred Juveniles in the Adult Criminal Court: The Direct and Interactive Effects of Race and Ethnicity. (April 2017) - Lehmann, Peter S.; Chiricos, Ted; Bales, William D.
Much prior research has demonstrated that race and ethnicity are associated with harsher punishment outcomes among adult defendants in the criminal court. However, few studies have explored these disparities in the sentencing of juvenile offenders who have been transferred to the adult court, and this research has reported conflicting findings. Moreover, the ways in which offenders' race and ethnicity may interact with their sex, age, and offense type have yet to be explored among this population. Analysis of defendants sentenced in Florida ( N = 30, 913) reveals that Black transferred juveniles are more likely to be sentenced to jail or prison and are given longer prison sentences than Whites, but Hispanic youth are only penalized in the sentence to jail. Interaction analyses suggest that Black males are sentenced particularly harshly regardless of age, and the effects of race and ethnicity are conditioned by a violent, sex, or drug offense.